First-Principles Calculations of the Pressure Stability and Elasticity of Dense TiO2 Phases Using the B3LYP Hybrid Functional - Swamy, Varghese; Wilson, Nicholas C (Journal of physical chemistry. C, 2014)
The crystal structures, pressure–volume equations of state, and pressure stability up to 100 GPa of the experimentally observed and theoretically proposed dense TiO2 phases (rutile, columbite, baddeleyite, OI, cotunnite, fluorite, pyrite, and Pca21) were calculated using the hybrid B3LYP exchange-correlation functional and two independent Gaussian-type basis functions. Overall, the B3LYP results are in good agreement with the experimental data on the structures and elastic properties. The B3LYP functional also shows superior performance relative to projector-augmented wave/pseudopotential-based planewave density functionals in predicting the elastic behaviors for most of the TiO2 phases with the exception of fluorite-TiO2. The latter structure shows significant sensitivity to the choice of basis functions. The order of phase stability with increasing pressure predicted by B3LYP is rutile → columbite → baddeleyite → OI → cotunnite, in agreement with available experimental results. In the pressure range of 20–50 GPa, the B3LYP total energy for the recently proposed Pca21 structure is very close to that for one or more of the accepted stable phases (columbite, baddeleyite, OI, and cotunnite), suggesting potential stabilization of the Pca21 structure at high temperatures. The B3LYP electron density-of-states projections suggest large band gaps for the high-pressure phases OI and Pca21.